Why English Isn't that Hard: Impact of Adopt-A-Friend Program on Students with Failing Grades - Oestar, Jennifer (Faculty of Teacher Training and Education, Universitas Terbuka, 2023)
The purpose of this study is to narrate the conditions of selective grade 10 students at-risk of failing English 10. This also deals with assessing the impact of Adopt-a-Friend Program on their academic performance and socialization in class. The study used qualitative method triangulated through observation, structured written and oral interview, and used of existing documents (F138) and journal entry. Students with failing grades were purposively chosen and paired with high performing students in a peer-tutoring approach. Although the target of the program are selected students at-risk of failing English subject, it was launched to all grade 10 students to eliminate stereotyping since academic grades became the basis for choosing the respondents. The study revealed that those students at-risk of failing English 10 benefited much from the program. Most of the responses revealed that they have improved their academic performance and socialization in class. Moreover, they suggested that the program must continue until the last quarter of the school year. Those high performing students who adopted them revealed that they enjoyed the program, however they suggested some improvements for Adopt-a-Friend Program’s next implementation. As a result, there is a significant increase in the performance of the student adoptee and adopted.